2010
DOI: 10.1145/1787234.1787254
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the popularity of online content

Abstract: We present a method for accurately predicting the long time popularity of online content from early measurements of user's access. Using two content sharing portals, Youtube and Digg, we show that by modeling the accrual of views and votes on content offered by these services we can predict the long-term dynamics of individual submissions from initial data. In the case of Digg, measuring access to given stories during the first two hours allows us to forecast their popularity 30 days ahead with remarkable accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
678
2
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 850 publications
(699 citation statements)
references
References 23 publications
13
678
2
6
Order By: Relevance
“…Of the many factors contributing to the exponential and significant increase in Internet usage, most researchers agree that the growth of Web content has made the most critical contribution (Huang, 2008;Leighton, 2009;Szabo & Huberman, 2010). Unlike offline mediums of communication (e.g., print media [newspapers, magazines]), the Web (online medium of communication) possess characteristics of high connectivity, interactivity, and global reach (Mulhern, 2009;Scarpi, 2012;Singh, Bansal, & Kaur, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Of the many factors contributing to the exponential and significant increase in Internet usage, most researchers agree that the growth of Web content has made the most critical contribution (Huang, 2008;Leighton, 2009;Szabo & Huberman, 2010). Unlike offline mediums of communication (e.g., print media [newspapers, magazines]), the Web (online medium of communication) possess characteristics of high connectivity, interactivity, and global reach (Mulhern, 2009;Scarpi, 2012;Singh, Bansal, & Kaur, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the linear growth in popularity is induced by the competition between memes, in contrast to the exponential growth at earlier times [ Fig. 2(a)] when the memes were not competing for the same resources [7,29].…”
mentioning
confidence: 99%
“…Cha et al [20,23] found that there is a strong correlation between the popularity of a video after two days and after ninety days. These observations were supported by a study performed by Szabo et al [5]. More recently, Chatzopoulou et al [24] studied the correlation between popularity and a wider range of metrics.…”
Section: Related Workmentioning
confidence: 52%
“…Several efforts have been made to apply this theory to the prediction of multimedia content popularity [4,5]. However, to our knowledge, these predictions have never been integrated into an actual cache replacement strategy.…”
Section: Introductionmentioning
confidence: 99%